Contraceptive awareness, patterns of use, and unmet contraceptive needs among pregnant women attending antenatal clinics in a tertiary care facility - Gurmeet, Pranaya; Dutt, Vipul; Deo, Jayant; Gupta, Vivek; Sharma, Rajesh; Madne, Ganesh; More, V. K.; Pandya, Kapil H.; Patel, Barun Bhai (International Journal Of Community Medicine And Public Health, 2026)
Background: The term unmet need for family planning is a central metric in reproductive health, guiding advocacy, policy formation, programme implementation, and monitoring of health outcomes globally. This study evaluated awareness, perceptions, and usage of contraceptive methods among pregnant women. Methods: A descriptive cross‑sectional study was undertaken among 384 third‑trimester antenatal attendees at a tertiary care hospital. Data were obtained using a pre‑validated questionnaire and analysed using SPSS v20 and Epi Info. Results: While 94.3% knew of at least one contraceptive method and 76% endorsed use to delay or avoid pregnancy, only 25.3% had ever practised contraception. The most frequently used methods reported were condoms (55%) and oral contraceptive pills (26%). Conclusions: Contraceptive knowledge and use were significantly associated with age over 20 years, higher education, employment, and better socioeconomic status (SES).